Serological Testing in Screening for Adult Celiac Disease - Helen Rachel Gillett; Hugh James Freeman (Canadian Journal of Gastroenterology)
Assays for celiac-related antibodies are becoming widely available, and the present review aims to clarify the use of these investigations in the diagnosis of, management of and screening for adult celiac disease. The sensitivities and specificities of various antibody tests are discussed, along with their clinical use as an adjunct to small bowel biopsy, and as a first-line investigation for patients with atypical symptoms of celiac disease or patients at high risk of developing sprue.